Perception of Climate Change and Impact on Land Allocation and Income: Evidence from Vietnam’s Delta Region - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The research has been completed. The paper has been accepted for publication in Agricultural and Resource Economics Review. Final version of the manuscript has been submitted to the journal and the paper is currently in press.